Diabetes-related cardiovascular and economic burden in patients hospitalized for heart failure in the US: a recent temporal trend analysis from the National Inpatient Sample - Menatalla Mekhaimar (14103708) (2020)
We aimed to study the cardiovascular and economic burden of diabetes mellitus (DM) in patients hospitalized for heart failure (HF) in the US and to assess the recent temporal trend. Data from the National Inpatient Sample were analyzed between 2005 and 2014. The prevalence of DM increased from 40.4 to 46.5% in patients hospitalized for HF. In patients with HF and DM, mean (SD) age slightly decreased from 71 (13) to 70 (13) years, in which 47.5% were males in 2005 as compared with 52% in 2014 (p trend < 0.001 for both). Surprisingly, the presence of DM was associated with lower in-hospital mortality risk, even after adjustment for confounders (adjusted OR = 0.844 (95% CI [0.828–0.860]). Crude mortality gradually decreased from 2.7% in 2005 to 2.4% in 2014 but was still lower than that of non-diabetes patients’ mortality on a yearly comparison basis. Hospitalization for HF also decreased from 211 to 188/100,000 hospitalizations. However, median (IQR) LoS slightly increased from 4 (2–6) to 4 (3–7) days, so did total charges/stay that jumped from 15,704 to 26,858 USD (adjusted for inflation, p trend < 0.001 for both). In total, the prevalence of DM is gradually increasing in HF. However, the temporal trend shows that hospitalization and in-hospital mortality are on a descending slope at a cost of an increasing yearly expenditure and length of stay, even to a larger extent than in patient without DM. Other Information Published in: Heart Failure Reviews License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10741-020-10012-6